Hair cortisol and cognitive performance in working age adults. (May 2016) - McLennan, Skye N.; Ihle, Andreas; Steudte-Schmiedgen, Susann; Kirschbaum, Clemens; Kliegel, Matthias
Highlights: Long term cortisol exposure was measured via hair cortisol concentration. Cognition was measured using a battery of 15 neuropsychological tests. Hair cortisol concentration was not associated with cognition in working age adults. Demographic and health variables did not moderate the non-significant relationships. Abstract: It has been hypothesized that prolonged exposure to high cortisol levels results in cognitive impairment. However, previous research into the relationship between cortisol and cognition has produced mixed results, most likely due to difficulties achieving valid estimates of long-term cortisol exposure based on salivary or plasma cortisol assessments at a single time point. Furthermore, there has been little research on the cognitive effects of long-term cortisol exposure in working-age adults. In the present study, hair samples were collected from 246 nurses (89.8% female) aged from 21 to 62 (M = 42.0, SD = 11.2). Hair cortisol concentrations (HCC) in the proximal 3-cm hair segment were analyzed providing an estimate of integrated cortisol secretion over the 3 month-period prior to hair sampling. Cognition was measured using a battery of 15 neuropsychological tests, measuring core dimensions of memory, inductive reasoning, processing speed, crystalized intelligence and major aspects of executive functioning. HCC was not significantly related to any of the cognitive abilities measured, either before or after controlling for potential moderators such as age, sex, education, health, well-being, work ability and burnout. Tests for nonlinear relationships also yielded non-significant results. Thus, despite the study being well powered, long term cortisol exposure did not appear to be related to cognitive performance in this sample of working-age adults, suggesting that long term cortisol exposure may be less relevant to cognition in younger and middle-aged adults than was previously thought.